A Robust Approach for Enhanced Autonomous Robot Navigation - Ismail, Sherif Khaled Mohamed Issa (2024)
A Master of Science thesis in Mechatronics Engineering by Sherif Khaled Mohamed Issa Ismail entitled, “A Robust Approach for Enhanced Autonomous Robot Navigation”, submitted in March 2024. Thesis advisor is Dr. Mamoun Abdel-Hafez. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).